A Study on Commercial Efficiency of Tamil Nadu Cooperative Sugar Mills - Ganesan, S. (Indian Journal of Marketing, 2007)
In emphasizing the importance of the sugar industry in the society, it may not be an exaggeration to say that there is none in the present day who does not taste the sugar directly or indirectly. Therefore, sugar is one of the consumption goods, which is required by everyone in the society for one's household purposes. Sugar industry is one of the best contributors of the revenue both to the central as well as the State Governments. The sugar factories located in various parts of the country work as nuclei for development of rural areas by mobilizing rural resources and generating employment, transport and communication facilities. Over 4.5 crore farmers, their dependants and a large mass of agricultural labour are involved in sugarcane cultivation, harvesting and ancillary activities. The sugar industry employs over 5 lakh skilled and unskilled workmen, mostly from the rural areas.